2012
DOI: 10.1002/job.1801
|View full text |Cite
|
Sign up to set email alerts
|

Observer reactions to interpersonal injustice: The roles of perpetrator intent and victim perception

Abstract: Summary The present research contributes to a growing literature on observer reactions to injustice experienced by others. In particular, we separated two variables that have previously been confounded in prior research, namely perpetrator intent to cause harm and victim perception of harm. We expected that injustice intent and injustice perceptions would have both unique and joint effects on observer reactions. The results of three experiments in which we manipulated perpetrator injustice intent and victim in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 63 publications
0
49
1
Order By: Relevance
“…Studies of thirdparty reactions to injustice have pointed to the importance of perceptions of the perpetrator's intention to harm the victim. Third-parties' perception of the intention to harm appears to influence punishment more than the victim's perception (Umphress et al 2013). Indeed, in criminal law, a person is judged liable depending on the degree of intentionality of the action (Malle, Guglielmo, & Monroe, 2014).…”
Section: Study 2: Extending Results In An Extreme Situation Of Interpmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of thirdparty reactions to injustice have pointed to the importance of perceptions of the perpetrator's intention to harm the victim. Third-parties' perception of the intention to harm appears to influence punishment more than the victim's perception (Umphress et al 2013). Indeed, in criminal law, a person is judged liable depending on the degree of intentionality of the action (Malle, Guglielmo, & Monroe, 2014).…”
Section: Study 2: Extending Results In An Extreme Situation Of Interpmentioning
confidence: 99%
“…Moreover, research on perpetrator intentionality suggests that intent drives thirdparty's reactions much more than actual harm (Umphress et al, 2013) and that third-parties may keep separate the perpetrator's motives from the harm inflicted to the victim (Chui & Dietz, 2014). However, in our manipulation, we varied the intentionality of the perpetrator (e.g., perseverance in shooting) at the same time as the harm inflicted (e.g., wounded-not wounded), making it impossible to determine whether one factor could have suppressed the effect of the other.…”
Section: Discussionmentioning
confidence: 99%
“…Our second contribution is to deontic justice theory and research on its implications for workplace dynamics. Extant research (Rupp, Shao, Thornton, & Skarlicki ; Skarlicki & Rupp ; Turillo et al ; Umphress, Simmons, Folger, Ren, & Bobocel ) has shown that individuals value justice not only for instrumental reasons (e.g., economic self‐interest and social standing within a group) but also for moral reasons (e.g., a belief that people should be treated fairly). In general, empirical findings have shown that people tend to have negative attitudinal, affective, and behavioral reactions toward those who violate the principled moral obligations of justice (Folger & Glerum ).…”
Section: Discussionmentioning
confidence: 99%
“…Ferris, Spence, Brown, and Heller (2012) reported finding that daily interpersonal injustice was positively related to daily workplace deviance. Researchers have also reported finding that higher levels of perception of interpersonal injustice were correlated with higher levels of violations of moral duty (Cropanzano & Mitchell, 2005;Umphress et al, 2013). It has been reported that covert aggressive behaviors are the most common forms of aggression in the workplace setting (Baron & Neuman, 1998;James et al, 2005).…”
Section: Interactional Injustice and Workplace Aggressionmentioning
confidence: 93%
“…Interactional injustice has two central elements: a) interpersonal injustice, and b) informational injustice. Interpersonal injustice refers to any treatment received by a subordinate from a superior in which a lack of respect and concern for the dignity of the individual is shown (Umphress, Simmons, Folger, Ren, & Bobocel, 2013). When employees are not provided with adequate explanations or information in a timely manner, informational injustice occurs.…”
Section: Interactional Injustice and Workplace Aggressionmentioning
confidence: 99%